Village Government Strategies in Branding Tourism Villages Through Digital-Based Social Mapping in South Tete Batu - Muhammad Ilham; Ikmal Maulana (Journal of Social Growth and Development Studies, 2025)
This study is motivated by the tourism industry’s significant potential to boost national income and economic growth in the era of globalization, particularly through the development of tourism villages. The East Lombok Regency government has implemented the policy "Fair, Prosperous, and Safe East Lombok," designating 91 tourism villages, including Tetebatu Selatan Village in Sikur District, known for its natural and cultural attractions. To ensure sustainable tourism, a strong branding strategy is essential. This study aims to examine the village government's efforts in branding Tetebatu Selatan Tourism Village through Digital-Based Social Mapping. A descriptive qualitative method was used, with data collected through observation, interviews, and documentation, validated using source triangulation. The findings reveal that the village government has mapped local potentials, such as English Village, Agriculture Village, Cultural Village, Religious Village, Fruit Village, and Aren Village, and has promoted branding through (tetebatuselatan.com) and (jadesta.com), a platform managed by the Ministry of Tourism and Creative Economy.